Analysis of Processing of Clove Essential Oil In Lawulo Village Samaturu Sub-District Kolaka District - Muhtar Amin (Agribusiness Journal, 2017)
The objectives of the study were to train clove farmers group about the post-harvest handling system in order to produce essential oils with export quality, to train clove farmers group in terms of essential oil processing system as well as to encourage clove farmers group to apply appropriate technology for processing of clove essential oil with export quality. In general, the main and most common problems faced by clove farmers are inadequate system of clove essential oil processing system, the handling system and equipment used are not up to standard, moreover, the technology used in handling, durability, and package of clove essential oils still very limited. The approaches offered and agreed by the clove farmer group are as follow: (1) General approach, (2) Determination of training participants, (3) Types and procedures of training (training strategy), and (4) Scale of the program. The expected targets and outcomes of this community service program are: Farmer groups are able to apply appropriate technology in the production of clove essential oil, both to post-harvest handling, processing and storage of clove essential oils to obtain added value. In fact, knowledge of farmers about post-harvest handling and processing technology of clove essential oil to increase farmer's income is still very poor. The results of analysis of essential oil clove processing showed that the clove leaves utilization as an effort to create an added value of farmer’s income by Rp. 13,000,000 per production unit. The difference in selling price between the dried clove leaves and processed clove leaves into essential oil was Rp. 10,765,000. Comparative test (t-test) showed that t-count value for selling dried clove leaves was 16,068 while clove leaves processed into essential oil was 35,108. The t-table value of 1,675 indicated that t count t table where H_0 is rejected and H_1 is accepted. It concludes that there is a comparative income of farmer who sells dried clove leaves and farmers who sell clove leaves in the form of essential oils.